If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1) = 3x + -19 Reorder the terms: (-1 + 2x) = 3x + -19 Remove parenthesis around (-1 + 2x) -1 + 2x = 3x + -19 Reorder the terms: -1 + 2x = -19 + 3x Solving -1 + 2x = -19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -1 + 2x + -3x = -19 + 3x + -3x Combine like terms: 2x + -3x = -1x -1 + -1x = -19 + 3x + -3x Combine like terms: 3x + -3x = 0 -1 + -1x = -19 + 0 -1 + -1x = -19 Add '1' to each side of the equation. -1 + 1 + -1x = -19 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = -19 + 1 -1x = -19 + 1 Combine like terms: -19 + 1 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| 10+3y=28 | | q^2=-45 | | 2(x+12)=27*6-12 | | -5/3(y-10)-1/4y= | | -5/3(y-10)-1/4y | | 6d+25=-5 | | 80=2r-7(11) | | 6x+3-72x=0 | | 0=-4w-31 | | (5x/x^5) | | [0.2*ln(580-Y)]+[0.8*ln(180-Y)]=ln(200) | | 10+3n=35 | | x^2+y^2-12x+4=0 | | 0=-48v+161 | | 4.2=x-83.5 | | 6t+3(1-3t)= | | 8(t-1)=6(t+3) | | 3x-2=4x+15 | | -5(x+2)-4=-29 | | Ad=12ax+14 | | n(n+1)(n-1)(n-2)=840 | | 1=g/2-2 | | (10n)3/2 | | 0=-5x-(625/10) | | -5=5-2d | | -w/3=12 | | 2B-11=88 | | -4/7x=16/27 | | 2v+1=10 | | 2x^2+2x+75=0 | | y/4=14 | | (2+w)(4w-5)=0 |